2017
DOI: 10.1186/s12877-017-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in management and outcomes in hospitalized healthy and well-functioning bacteremic pneumococcal pneumonia patients: a cohort study

Abstract: BackgroundLimited data are available regarding fit and healthy patients with pneumonia at different ages. We evaluated the association of age with clinical presentation, serotype and outcomes among healthy and well-functioning patients hospitalized for bacteremic pneumococcal community–acquired pneumonia.MethodsWe performed a prospective cohort study of consecutive healthy and well-functioning patients hospitalized for this type of pneumonia. Patients were stratified into younger (18 to 64 years) and older (≥6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
11
3
2
Order By: Relevance
“…A study conducted in the Netherlands in 2016 had similar results, with an average length of hospital stay of 12 days. (10) Ruiz et al identified a mortality risk in the ICU of 4.2 (p = 0.10); (8) however, in our study, the in-hospital mortality was higher (OR: 156.3) because all 37 patients who died were in the ICU.…”
Section: /7contrasting
confidence: 74%
See 2 more Smart Citations
“…A study conducted in the Netherlands in 2016 had similar results, with an average length of hospital stay of 12 days. (10) Ruiz et al identified a mortality risk in the ICU of 4.2 (p = 0.10); (8) however, in our study, the in-hospital mortality was higher (OR: 156.3) because all 37 patients who died were in the ICU.…”
Section: /7contrasting
confidence: 74%
“…This outcome may be related to immunosenescence because the participants were healthy and functional elderly people. (8) The presence of chronic diseases influences both the chance of acquiring PP because of changes in immune response and the severity of the disease and its outcomes. Patients with comorbidities have a high rate of pneumococcal disease-related mortality in short-(30 days) and long-term (1 year) periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…outras patologias associadas. A pneumonia em pacientes idosos necessita de ser acompanhada de perto, pois há maior risco de evolução para quadros mais graves, Estes resultados são condizentes com os achados de Ruiz et al(19) onde comparam adultos de 18 a 64 anos e idosos ( ≥ 65 anos de idade) diagnosticados com pneumonia, e constataram que pacientes com idade maior que 65 anos apresentavam uma taxa de mortalidade maior em 30 dias de internação; entretanto, os idosos que foram internados com menor frequência em unidades de terapia intensiva tiveram menor tempo de internação hospitalar.…”
unclassified
“…Some individuals infected with COVID-19 may develop COVID-related pneumonia, a serious complication in which the air sacs within the lungs become infected. If pneumonia develops, patients may experience a phlegm-filled cough in addition to COVID-19 symptoms[4].…”
mentioning
confidence: 99%